2023
DOI: 10.1175/waf-d-22-0217.1
|View full text |Cite
|
Sign up to set email alerts
|

The Development of a Consensus Machine Learning Model for Hurricane Rapid Intensification Forecasts with Hurricane Weather Research and Forecasting (HWRF) Data

Abstract: This study focused on developing a consensus machine learning (CML) model for tropical cyclone (TC) intensity-change forecasting, especially for rapid intensification (RI). This CMLmodelwas built upon selected classical machine learning models with the input data extracted from a high-resolution hurricane model, the HurricaneWeather Research and Forecasting (HWRF) system. The input data contained 21 or 34 RI-related predictors extracted from the 2018 version of HWRF (H218). This study found that TC inner-core … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…(2015); henceforth referred to as KRD15). Ko et al (2023) explored the application of a consensus machine learning (CML) model in TC intensity change forecasting and indicated the CML exhibits better performance on RI predictions compared to the operational models such as SHIPS, GFS. Narayanan et al (2023) proposed a simple deterministic binary classification model based on the cooccurrence of environmental parameters (MCE) to predict an RI event.…”
Section: Assessment Of Model Predictive Performancementioning
confidence: 99%
See 2 more Smart Citations
“…(2015); henceforth referred to as KRD15). Ko et al (2023) explored the application of a consensus machine learning (CML) model in TC intensity change forecasting and indicated the CML exhibits better performance on RI predictions compared to the operational models such as SHIPS, GFS. Narayanan et al (2023) proposed a simple deterministic binary classification model based on the cooccurrence of environmental parameters (MCE) to predict an RI event.…”
Section: Assessment Of Model Predictive Performancementioning
confidence: 99%
“…Before the applying ML methods in TC intensity forecasting, it is known that the statistical-dynamical-based forecast models using climatological, persistence, and numerical model predictors provide the highest skill in intensity (Goldenberg et al, 2015;Kim et al, 2018). Yamaguchi et al, 2018;Xu et al, 2021;Ko et al, 2023). The statistical-dynamical model developed by Kim et al (2018) showed the smallest mean absolute errors at short lead time (up to 24 h) for TC intensity prediction compared to operational dynamical forecast models (Kim et al, 2018).…”
mentioning
confidence: 99%
See 1 more Smart Citation